2020
DOI: 10.17233/sosyoekonomi.2020.01.05
|View full text |Cite
|
Sign up to set email alerts
|

Neo-Kurumsal Perspektif ile Vergi Uyumsuzluğunu Anlamak: Türkiye’deki Bir Kamuoyu Araştırmasından Bulgular

Abstract: Conventionally, those engaging in tax non-compliance are explained as rational economic actors doing so when the benefits outweigh the costs. However, many individuals are still compliant to their tax regimes even when the pay-off from tax evasion is greater than the costs. The result is the emergence of a social actor perspective that gives primacy to tax morale when explaining tax noncompliance. Through the lens of neo-institutionalist theory, this approach argues that citizens behave in ways that reflect th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 54 publications
0
1
0
2
Order By: Relevance
“…Percepção da probabilidade de detecção da evasão fiscal (auditorias). (Kayaoglu & Williams, 2020) efetividade da fiscalização (Fisco) RD1 utilização da informatização na fiscalização RD2 suficiência de auditores para fiscalização RD3 controle e monitoramento contínuo da fiscalização (Fisco) RD4…”
Section: Risco De Detecçãounclassified
See 1 more Smart Citation
“…Percepção da probabilidade de detecção da evasão fiscal (auditorias). (Kayaoglu & Williams, 2020) efetividade da fiscalização (Fisco) RD1 utilização da informatização na fiscalização RD2 suficiência de auditores para fiscalização RD3 controle e monitoramento contínuo da fiscalização (Fisco) RD4…”
Section: Risco De Detecçãounclassified
“…Percepção do nível de penalidades aplicadas pelas autoridades tributárias. (Kayaoglu & Williams, 2020) impacto das penalidades sobre a reputação SP1 severidade das multas SP2 rigor das punições SP3 geral do rigor das punições SP4 efetividade da penhora como penalidade tributária. SP5…”
Section: Severidade Das Puniçõesunclassified
“…Various studies on the education level of taxpayers has established that education has a strong (positive relationship) effect on increasing the awareness of taxpayers' as well as tax compliance behaviour (Kayaoglu & Williams, 2020;Mansor & Gurama, 2016;Kasipillai et al, 2000;McGee & Bose, 2007;Al-Ttafi, 2009;Palil & Mustapha, 2011;Palil, Akir, & Ahmad, 2013). On the other hand, some studies have indicated that the higher the level of education of taxpayers, the lower the anticipated rate of compliance (Ross & McGee, 2011;Yalama & Gumus, 2013).…”
Section: Education Levelmentioning
confidence: 99%